Improving CCT-D and LO of the 6600K ICP-WLEDs by K2SiF6:Mn4+ Phosphor - Phu Tran Tin; Anh Vu Le; Minh Tran; Nguyen Huu Khanh Nhan; Tran Thanh Trang (Institute of Advanced Engineering and Science, 2019)
In this research, we propose a novel recommendation for improving CCT-D and lumen output (LO) of the 6600K in-cup packaging white LEDs (ICP-WLEDs) by varying its particle concentration. By using Light Tools and Mat lab software based on the Mie Theory, we derive the influence of the red phosphor particle’s concentration on the D-CCT and LO. The results show that the CCT-D are significantly affected when the concentration of the red phosphor varying from 0% to 1.8%. The CCT-D decreases from 4000K to 2200K and LO increases from 800 lm to 1300 lm.